Strain-specific chemotaxis of Azospirillum spp. - Reinhold, B (1985)
Chemotactic responses of three Azospirillum strains originating from different host plants were compared to examine the possible role of chemotaxis in the adaptation of these bacteria to their respective hosts. The chemotaxis to several sugars, amino acids, and organic acids was determined qualitatively by an agar plate assay and quantitatively by a channeled-chamber technique. High chemotactic ratios, up to 40, were obtained with the latter technique. The chemotactic response did not rely upon the ability of the bacteria to metabolize the attractant. Rather, it depended on the attractant concentration and stereoconfiguration. Chemotaxis was found to be strain specific. Differences were particularly observed between a wheat isolate and strains originating from the C4-pathway plants maize and Leptochloa fusca. In contrast to the other two strains, the wheat isolate was strongly attracted to D-fructose, L-aspartate, citrate, and oxalate. The other strains showed maximal attraction to L-malate. The chemotactic responses to organic acids partially correlate with the exudation of these acids by the respective host plants. Additionally, a heat-labile, high-molecular-weight attractant was found in the root exudates of L. fusca, which specifically attracted the homologous Azospirillum strain. It is proposed that strain-specific chemotaxis probably reflects an adaptation of Azospirillum spp. to the conditions provided by the host plant and contributes to the initiation of the association process.